A declaration and constitution for a free society : making the Declaration of Independence and U.S. Constitution fully consistent with the protection of individual rights /: making the Declaration of Independence and U.S. Constitution fully consistent with the protection of individual rights. (2021) - Simpson, Brian P, 1966-
No abstract available